Prototype Konveyor Seleksi Objek Berdasarkan WarnaMenggunakan Kamera Pixy Cmucam 5 Berbasis Arduino - Ridha, Muhammad, Ir. Pratomo Budi Santoso, MT (2016)
In the developing of packaging industry, the sorting of the goods that is done in the end will select the object based on the color. The sorting that is done manually now has been left in industry, because it will take a long time and not so eficient and cause high error. Therefore, in order to desain aw automatic technique in industry, to determine the color of the object and to sort, the sensor of Camera Pixy Cammu5 is used. By using Camera which is Pixy Cammu5, the degree of accuracy increases and the distance is gettig to far than the sensor of color so close. This dence is run uder arduino mega as the place of unit processing to proceed the data and as control to control the motor DC, servo and pixy cammu5 camera. The function of motor the DC is control conveyor while the motor servo is functioned to control the result of detected object. The result of this observation is to sort the object accordance with the color detection with ahighe accuracy compare to a color sensor. Conveyor rotates when PWM minimum 100, if it is under 100 the object can't be detected. The detection of object based on the coulour reaches 100% when PWM 100-125. When PWM is over 125, the conveyor rotates but the camera can't detect object because the conveyor is too fast.